BIO-ECOLOGICAL DIFFERENCES OF CISTANCHE SALSA IN CONDITIONS OF KARAKALPAKSTAN - Baltabaev.M; Otenova.F (Scholar Express Journals, 2022)
In the literature, members of the genus Cistanche salsa (Chenopodiaceae) of the Chistanche family, in particular, halloxylon, are parasitize on the roots of Circassian plants. There are 9 species of this genus in Uzbekistan and 4 species in Karakalpakstan, all of which are parasitic plants
Keywords: perennial herbaceous plants; unbranched stem covered with scales; flowers are collected in brushes